ضمانات المشتري في عقد البيع على التصاميم - بوزوايد, وفاء; زلاسي, جهاد; نصيب, شهرزاد (University of Eloued جامعة الوادي, 2023)
أن المشرع الجزائري أوجب مطابقة الأشغال المنجزة لأحكام رخصة البناء المسلمة فلا يمكن حيازة بناية أو جزء منها من طرف المقتني إلا بعد تسليم شهادة المطابقة في القانون رقم 90-25 المؤرخ في 01/12/1990، والقانون رقم 08-15 المؤرخ في 20/07/2008 فتسلم شهادة المطابقة في أجل 23 يوما إبتداء من تاريخ المعاينة بين محضر الجزء ومطابقة الأشغال المنجزة لرخصة البناء المسلمة، وألزم المشرع الجزائري المرقي العقاري تحقيق للمشتري (المقتني) ضمان الإنتفاع بالبناية حسب الطبيعة التي أعدت من أجلها وتأكيد الإنتفاع الهادئ من خلال ضمان حسن يسر عناصر التجهيز الذي نصت عليه المادة 15 من المرسوم التشريعي رقم 93-03 هذا الضمان ملقى على عاتق المرقي العقاري لمدة سنة إبتداء من حيازة البناية المنجزة .The Algerian legislator required that the completed works comply with the provisions of the issued building permit. A building or part of it cannot be acquired by the acquirer except after submitting a certificate of conformity in Law No. 90-25 of 12/01/1990, and Law No. 08-15 of 07/20. /2008 The conformity certificate was received within 23 days, starting from the date of inspection between the part record and the conformity of the completed works to the delivered building permit. The Algerian legislator obliged the real estate promoter to ensure that the buyer (acquirer) can use the building according to the nature for which it was prepared and to confirm quiet use through a guarantee of good comfort. The equipment elements stipulated in Article 15 of Legislative Decree No. 93-03. This guarantee is the responsibility of the real estate promoter for a period of one year starting from possession of the completed building.
مذكرة ماستر
Keywords: عقد البيع – التصاميم – ضمانات المشتري: sales contract - designs - buyer guarantees